Kemampuan Mahasiswa Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP UIR dalam Menentukan Jenis Kalimat - S, Ermawati.; Hermliza, Hermaliza; Aprilla, Yaiza Ike (GERAM: Gerakan Aktif Menulis, 2020)
This research was related to the ability of students of Indonesia language and literature education in determining the type of sentence. It was conducted because obstacles were still found such as students could not distinguish simple items related to the type of sentence, especially in terms of the number of clauses and syntactic forms. The problems in this research were; (1) how was the ability of students of Indonesia language and literature education study program at FKIP UIR in determining the type of sentence based on the number of clauses?; (2) how was the ability of students of Indonesia language and literature education study program at FKIP UIR in determining the type of sentence based on the syntactic form?. Thus, this research aimed to find, analyze, describe, and conclude the ability of students of Indonesia language and literature education study program at FKIP UIR in determining sentence types based on the number of classes and their syntactical forms. The population in this research was all fourth semester that consist of 149 students and the sample was 15%, namely 22 students. Data collection techniques included observation and questionnaire. The theory used refers to the opinion expressed by Alwi, et al (2003) and other expert opinions. Based on the analysis conducted it can be concluded that; (1) The ability of students of Indonesia language and literature education study program at FKIP UIR in determining the type of sentence on the number of clauses based on the students’ average test score was 81.36 which was categorized “excellent”; and (2) The ability of students of Indonesia language and literature education study program at FKIP UIR in determining the type of sentence on the syntactic form based on students’ average test score was 79.31 which was categorized “good”.